Study on Green Products Innovation of Fashion SME “NP” - Ginting, Griba Raymundo; Tampubolon, Lamtiur Hasianna (UI Scholars Hub, 2021)
Innovation is a social and economic success due to the discovery of new solutions that significantly improve value offered to customers and benefits perceived by customers with cost exchanges as profits. Therefore, innovation becomes a competitive advantage for MSME to have the ability to compete and survive in dynamic markets. The purpose of this research is to examine innovations in the green products of MSME Fashion. The research uses qualitative methods with semi-structured interviews and observations. Data is obtained through in-depth interviews with three informants namely the owner and two employees of Fashion SME and triangulation to two consumers of the Fashion SME. The results of this research shows that innovations of green products conducted by Fashion SME have achieved innovation successes. The successes of such innovations include business success, technical success, and financial success. In addition, entrepreneurial proactiveness plays a very important role in developing sustainable innovation so that consumers are not saturated, and still developing innovations to be a competitive advantage of the company, both in terms of service and product quality.